Efeito do tratamento preservativo com CCA-C na estabilidade dimensional da madeira de Eucalyptus - Arantes, Lorran de Sousa (2016)
The objective of this study was to evaluate in which extent the preservative treatment with CCA-C (Arsenide chromated copper type C) affects the dimensional stability of Eucalyptus wood treated in autoclave. Were used 14 fence post of Eucalyptus urophylla x E. grandis, selected due their humidity. After selecting the fence post and before the preservative treatment, discs with 5 cm thickness were removed from the two ends of the fence post and one disc in the central portion of the fence posts, which were used for determination of humidity, basic density and dimensional stability. After removing small logs, they were properly identified and submitted to the preservative treatment in autoclaving. Soon after the small logs preservative treatment, were removed discs with 5 cm thickness from the end of the short logs and used in retention tests by atomic absorption spectrophotometry and determination of dimensional stability of the wood. To evaluate the effect of CCA-C on the dimensional stability of the wood, it was made comparison between averages of wood treated with CCA-C and untreated woods, applying the Student test at 5% probability. It also evaluated the effect of retention on the dimensional stability of wood treated with CCA-C through Pearson correlation analysis and linear regression. It was found that the preservative treatment with CCA-C did not improve the dimensional stability of Eucalyptus urophylla x E. grandis. Despite the weak correlation with retention, tangential swelling suffered the greatest influence by the preservative treatment with CCA-C.